La lectura animada como estrategia para el fortalecimiento de la participación y responsabilidad democrática (2018)
In the project entitled: "The animated reading as a strategy for strengthening democratic participation and responsibility aims to analyze the strengthening of participation and democratic responsibility through animated reading. This is because the students show low participation in oth the curricular activities and the curricular extras of the institution being not responsible at the time of making decisions. In such a way that this research work takes as a central problem the conflicts between peers, aggressive reactions, little respect for the opinion of the other and little listening, which occur in the fifth-grade population. Instruments were used such as: direct and indirect observation, the survey among others; collecting the necessary information to proceed to olve the problem. To make this study possible, it was necessary to use the qualitative research approach, and among the results we can mention that it was found low acceptance rates and respect for the participation of others and indeed the use of animated reading as a pedagogical trategy allows to improve participation and democratic accountability in schools, therefore students are facilitated to learn to communicate in a different way; where dialogue, attitude and way of thinking help them identify new ways to solve daily conflicts not only in the classroom but outside of it, learning to live together and accept the opinions of others in a harmonious way